Effect of storage temperature and type of packaging on physical and chemical quality of carrot. Issue 1 (February 2020) - Asgar, A
Abstract: Carrot can get damaged during harvesting or during storage which can reduce the quality. The research was conducted in the laboratory of post-harvest Vegetable Crops Research for the month of May-July 2016. The research aimed to analyze the effect of storage temperature and type of packaging on the characteristic of carrot. Factorial randomized block design with 4 x 4 and 2 replications was used in the study. The first factor was storage temperature consisted of 5 °C, 10 °C, 15 °C and room temperature. The second factor was the packaging comprised of polypropylene, polyethylene, wrapping, and non-packaging. Results showed that storage temperature affected water content, respiration rate, hardness, and weight loss in 3 weeks and 4 weeks of storage. Packaging affected on water content, vitamin C, respiration rate, and weight loss in 3 weeks, and 4 weeks. The temperature of 5 °C was the storage temperature that could maintain changes in the characteristics of the carrot. Polypropylene plastic type was an excellent package in maintaining changes in the characteristics of carrots during the storage process.